Design for reusability of medical equipment for optimal modularization using an endoscope as case study. Issue 1 (1st January 2019) - Aguwa, Celestine; Monplaisir, Leslie; Turgut, Ozgu; Jordan, Will; Etu, Egbe-Etu
Abstract: The reprocessing of reusable medical equipment (RME) is complex due to the difficulty of eliminating infections. Healthcare providers have expressed dissatisfaction with the difficulty faced in cleaning and disinfecting medical equipment after use. Reprocessed RMEs include endoscopes, valves, adapters etc. This research aims to increase the ease of reprocessing and decrease the risk of infection using a collaborative modular architecture framework. The methodology is divided into four steps. First, we identify and define the product's functional and physical decompositions. Secondly, based on stakeholders' input, parameters such as design, human factors, and cost were identified to be the main factors affecting the reprocessing of an endoscope. The parameters' subsequent metrics are selected for performance requirements. Thirdly, surveys are developed to collect data about the performance of different endoscope models. Fourthly, we utilize a linear multi-objective optimization model which aims at generating representative solutions on the true Pareto front of the problem that maximizes the similarity among module members in terms of the factors. Finally, we combine the module information with efficiency feedback to derive recommendations for the users. A case study is presented using hospital data. The results indicate that there is a high risk of infection caused by human errors during reprocessing for endoscopes clustered in Module 1 compared to Module 2 and 3 . To ensure that the safety and quality of medical care rendered to patients are not compromised, we recommend that healthcare providers utilize endoscopes in Modules 2 and 3 as they are safe and easy to reprocess.